A case of a death caused by an atrial-oesophageal-thoracic fistula after radiofrequency ablation of atrial fibrillation. (August 2022) - Wu, Qi-Long; Wang, Qi; Guo, Gao-Xian; Li, Yong-Guo; Xing, Yu; Zhao, Min-Zhu; Li, Hongwei; Li, Jian-Bo
Abstract: The report is about a 49-year-old man with rheumatic heart disease and atrial fibrillation. He underwent mitral valve replacement, tricuspid valvuloplasty, and atrial fibrillation radiofrequency ablation in the hospital. He vomited blood on the 2nd postoperative day, and the bleeding gradually worsened thereafter. He had to have repeated drainage of large amounts of blood from his right thoracic cavity and digestive tract. He died suddenly after undergoing an oesophageal endoscopy on the 24th postoperative day. The autopsy revealed an atrial-oesophageal-thoracic fistula. By excluding the possibility of the fistula being caused by complications from nasoenteric feeding, tracheal intubation, and a foreign body ingestion, we determined that the atrial-oesophageal-thoracic fistula was a complication after radiofrequency ablation according to the finding of coagulation necrosis of the myocardial cells at the left atrium fistula. In addition, we also performed an elemental analysis on the radiofrequency ablation area and other cardiac tissues by scanning electron microscopy-energy dispersive spectroscopy (SEM–EDS) and found five metal elements, Cr, Cu, Zn, Mn, and Ti, which specifically existed in the radiofrequency ablation area. This finding has the potential to serve as new evidence for radiofrequency ablation and is a worthy direction of research. Highlights: This article is the first report of an atrial-oesophageal-thoracic fistula complicated by radiofrequency ablation. Residual metal elements in the endocardium may be used as a basis for forensic diagnosis of radiofrequency ablation complications.